Case report: second phalanx fracture in a Colombian creole horse - Giraldo Botero, Lucas (2020)
The case of a 4.5-year-old Colombian Creole female equine was brought to the clinic with suspected transverse and vertical comminuted fracture of the second phalanx in the right forelimb with three days of evolution. Upon clinical examination, claudication of the affected limb was observed, categorized as 4/5, presenting inflammation and swelling related to the coronary impeller. An orthogonal radiographic study was performed at the pastern level in the affected limb, finding a comminuted vertical fracture related to the dorsal aspect of the second phalanx and a transverse fracture in the palmar portion. It was decided to perform orthopedic surgery to reduce de fracture and to apply osteosynthesis material. The patient responded satisfactorily to surgical treatment. Orthopedic clinical follow-up was performed for two months, obtaining complete recovery of the patient.